Haemoglobin and transferrin types of some West African cattle - Braend, M.; Khanna, N.D. (Cambridge University Press, 1968)
Polymorphic blood traits are very useful for studies of evolution, relationship and structure of breeds. Some of the systems are particularly valuable when no family data are available because the genotype can be determined directly. This paper reports the results of investigations of haemoglobin (Hb) and transferrin (Tf) types in the Muturu, N'Dama, Gudali and Red Mbororo breeds of Nigeria.The Hb gene frequencies were: Muturu, HbA = 0.72, HbD = 0.28; Gudali, HbA = 0.06, HbB = 0.32, HbC = 0.08; Red Bororo, HbA = 0.54, HbB = 0.44, HbC = 0.02. Transferin studies showed six different Tf phenotypes in Muturu their distribution being in agreement with the occurrence of the alleles TƒA, TƒD¹ and TƒD². In N'Dama the nine different Tf phenotypes were observed and explained by the alleles TƒA, TƒD¹, TƒD², and TƒE. In the Gudali 15 different phenotypes were found with distribution in agreement with the occurrences of the alleles TƒA, TƒB, TƒD², TƒF and TƒE. All alleles in this breed occurred at 0.1. In a limited number of Red Bororo cattle nine Tf phenotypes were seen. Their distribution can be explained by the occurrence of six genes: TƒA, TƒB, TƒD¹, TƒD², TƒF and TƒE.